Successful sequential management of traumatic choledochal leak and stenosis in children using ERCP: a case report and literature review - Leng, Cuo; Zou, Yu; Yang, Zhoujian; Zhao, Xinhua (Frontiers in Medicine, 2024)
Traumatic Choledochal Leak and Stenosis in Children is a relatively rare bile leakage, ***and there is no report of endoscopic retrograde cholangiopancreatography [ERCP] bile duct stent treatment in 3 years old, which avoids ***procedure and biliary tract modifications after the failure of conservative treatment of bile leakage, and solves the previous need for ***procedure in a minimally invasive or even non-invasive way. At the same time, it can be concluded that identifying the signs of conservative treatment failure is important, and ERCP is superior to CT and MR in diagnosing traumatic biliary leak in young children. Traumatic bile leakage common bile duct inflammatory stenosis, brittle tissue, not suitable for expansion, the choice of 5 Fr to 10 Fr plastic stent sequential treatment is an effective regimen. At the same time, it is necessary to closely monitor the biliary patency after ERCP to understand the long-term postoperative efficacy. ***Comprehensive evaluation before ***ERCP and detailed post ERCP monitoring require the participation of pediatricians.